POTENSI DAMPAK USAHA LAUNDRY KILOAN TERHADAP LINGKUNGAN HIDUP TERKAIT LIMBAH DAN PEMAANFAATAN AIR TANAH DI KECAMATAN DEPOK - , RONY ARYONO PUTRO, Abdullah Abdul Patah, SH., LL.M. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A research with title âPotential Impact Of Laundry Per Kilos Business On Environmental In Relation To Waste And Utilization Of Ground Water In Kecamatan Depok.â aimed to know the potential impact of business laundry kilograms to environment from two sites. There are disposal waste and the use of ground water. The research background is about a significantly extensive increasing number of businesses Laundry in Sleman Regency especially in the Kecamatan Depok. This research is an combination between personal empirical law with legal normative value. The process of data collection doing by field observation and study the books documents. Data clarification is according to the discussion and the obtained data analyzed in qualitative, then poured into the form of description. Based on the best part results of research correspondent most appeared to fulfill their water relied on the Ground Water with a drilled well and absorbing well. Only a few businessmen who has a mechanism to the liquid waste management remains production. Detergent as part of the washers machine have some components building a harmful blocks to the environment. One of the impact is help spur growth water hyacinth and water weed. An explosion in the amount of these crops will lead to silting up and stop the flow of water river. Plants that cover the surface of the water will hamper the entry sunâs ray and oxygen to the water